2022
DOI: 10.1097/scs.0000000000008868
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning in Metopic Craniosynostosis: Does Phenotypic Severity Predict Long-Term Esthetic Outcome?

Abstract: Background: There have been few longitudinal studies assessing the effect of preoperative phenotypic severity on long-term esthetic outcomes in metopic craniosynostosis. This study evaluates the relationship between metopic severity and long-term esthetic outcomes using interfrontal angle (IFA) and CranioRate, a novel metopic synostosis severity measure. Methods: Patients with metopic craniosynostosis who underwent bifrontal orbital advancement and remodeling between 2012 and 2017 were reviewed. Preoperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…The recessed temporal areas are often a residual sequela even after prolonged helmet molding. It has also been shown that more severe objective preoperative metopic phenotypes are associated with worse esthetic dysmorphology, 14 which correlates with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…The recessed temporal areas are often a residual sequela even after prolonged helmet molding. It has also been shown that more severe objective preoperative metopic phenotypes are associated with worse esthetic dysmorphology, 14 which correlates with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies reveal high degrees of subjectivity bias and low interrater reliability for popularly used methods (eg, Whitaker classification system). 5–7 Such variability and disagreement in appraising preoperative dysmorphology and appraising postoperative results renders determining surgical efficacy and comparing outcomes of different techniques difficult. Although two-dimensional normative measurements such as Farkas norms provide normative data for linear measurements, challenges persist in quantifying three-dimensional features, such as temporal retrusion, frontal bossing, and occipital bulleting.…”
Section: Discussionmentioning
confidence: 99%
“…Current popular methods of assessing postoperative results are subjective or demonstrate poor interrater reliability, even among experts. 4–6 Perhaps the most popular and widely adopted system for appraising postoperative craniofacial surgery outcomes is the Whitaker classification system, which assigns a score ranging from 1 to 4 based on the magnitude of subsequent surgery required to achieve aesthetic “normalcy.” 7 However, the Whitaker classification has demonstrated poor interrater reliability, likely secondary to its subjective nature and its pairing of an aesthetic appraisal to surgical management. 5,7 These subjective methods render appraising the quality of postoperative results or comparing the efficacy of surgical techniques difficult.…”
mentioning
confidence: 99%
“…11,12,[17][18][19][20][21][22] These measures and three-dimensional (3D) cranial morphometric analysis are combined in the CranioRate machine learning model that is now used by surgeons to measure metopic severity. [23][24][25][26] Our group recently proposed the supraorbital notch-nasionsupraorbital notch (SNS) notch angle as a meaningful measurement for identifying MCS and quantifying its severity. The purpose of this study is to validate the SNS angle using surgeon questionnaire responses, as well as the CranioRate tool.…”
Section: Introductionmentioning
confidence: 99%